2018
DOI: 10.1007/s00357-018-9251-4
|View full text |Cite
|
Sign up to set email alerts
|

A Multivariate Logistic Distance Model for the Analysis of Multiple Binary Responses

Abstract: Abstract:We propose a Multivariate Logistic Distance (MLD) model for the analysis of multiple binary responses in the presence of predictors. The MLD model can be used to simultaneously assess the dimensional/factorial structure of the data and to study the effect of the predictor variables on each of the response variables. To enhance interpretation, the results of the proposed model can be graphically represented in a biplot, showing predictor variable axes, the categories of the response variables and the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In that case, (v r1m − v r0m ) = 1 for the dimensions to which response variable r pertains. For this constrained model, Worku and De Rooij (2018) showed that the parameters can be estimated using standard software for logistic regression by using a structured design matrix for the predictors. This paper describes them as members of a larger family of models, the MELODIC family.…”
Section: Constrained Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…In that case, (v r1m − v r0m ) = 1 for the dimensions to which response variable r pertains. For this constrained model, Worku and De Rooij (2018) showed that the parameters can be estimated using standard software for logistic regression by using a structured design matrix for the predictors. This paper describes them as members of a larger family of models, the MELODIC family.…”
Section: Constrained Modelsmentioning
confidence: 99%
“…Moreover, q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q D0 D1 M0 we lay a dimensional structure on the response space. A standard GEE model would be equal to our one-dimensional model, with the constraint that all responses are equally well discriminated (see Worku and De Rooij, 2018). Ziegler et al (1998) discuss a set-up where the predictor variables have different effects on each of the response variables.…”
Section: Related and Competing Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…The family extends the recently proposed multivariate logistic distance models [69] which built on earlier logistic distance models [20,57,59] and can be considered as examples in the "Gifi goes logistic" framework as laid out by De Leeuw [17] and Evans [24].…”
Section: Introductionmentioning
confidence: 99%
“…When categorical response variables are considered, multivariate logistic regression models are usually appropriate. Examples include logistic regression models estimated using a generalized estimating equation (Zeger, Liang, & Albert, 1988) approach, or the multivariate logistic distance model (Worku & De Rooij, 2018) that considers a dimensional structure of the response variables.…”
Section: Introductionmentioning
confidence: 99%